Diterpenoids from Fokienia hodginsii. - Hau, Dang Viet; Tam, Nguyen Thanh; Quan, Tran Duc; Thien, Dao Duc; Tinh, Bui Xuan; Hong Nhung, Le Thi; Loc, Tran Van; Sung, Tran Van; Thuy, Trinh Thi (Vietnam Journal of Chemistry, 2017)
In continuous research on the chemical constituents of the twigs and leaves of Fokienia hodginsii (Dunn) A. Henry et Thomas growing in Highland, Lam Dong province 4 diterpenoids, including 3-oxo-totarol (totarolone, 1), 3β-hydroxytotarol (2), 15-nor-labda-8(17),12E-diene-14-carboxaldehyde-19-oic acid (3) and 13-oxo-15,16-dinorlabda-8(17),11E-diene-19-oic acid (4) were isolated. Their structures were elucidated by the spectroscopic methods and comparison with reported data. This is the first report on the isolation of compounds 1, 2 and 3 from this plant. Keywords. Fokienia hodginsii; totarane; nor-labdane diterpenoid.